Energy levels in rations for growing and finishing swine - Costa, Valdomiro; Fialho, Elias Tadeu; Freitas, Alfredo Ribeiro de (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was carried out at the Centro Nacional de Pesquisa de Suínos e Aves, in Concórdia, SC, Brazil, from August to November, 1983. The objective was to study the performance and carcass characteristics of swine fed with rations varying in digestible energy contents, 3,150; 3,300; 3,400 and 3,600 kcal DE/kg, combined with 16 and 14% of crude protein during the growing and finishing periods, respectively. One hundred and twenty eight pigs were used (64 barrows and 64 gilts), with initial average weight of 21.4 ± 0.5 kg, penned in, groups of four per pen. A digestion trial was conducted with 12 pigs weighing 24.8 ± 0.6 and 12 with 69.0 ± 0.5 kg. For the entire period, the average daily gain (0.860, 0.846, 0.846, 0.890 kg) was not influenced by treatments, but feed conversion (2.94, 2.85, 2.88, 2.63) improved linearly (P < 0.05) with the increasing level of energy content in the rations. The lowest energy diet produced carcasses with less backfat thickness, larger loin eye area, and lower ratio of fat to lean (P < 0.05). Barrows grew significantly faster, consumed more feed, had a significantly lower loin eye area, and higher fat to lean ratio than gilts. Digestibility of dry matter and crude protein were both increased by increasing levels of energy in the rations.